ANALISIS WACANA KRITIS MODEL TEUN A. VAN DIJK TERHADAP LIRIK LAGU ANAK KARYA AT MAHMUD - Muhammad Thobroni; Hari Bakti Mardikantoro; Rustono Rustono (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
This article aims to analyze the lyrics of children's song composed by AT. Mahmud to find out the relationship between the text and factors beyond the text. A critical discourse analysis (CDA) approach from Teun A. Van Dijk model is use as the tool of analysis. The results showed that in the macro structure as the analysis text, the song lyrics have the theme of the environment and the harmony of life. Superstructure, the arrangement of verse by stanza of interrelated lyrics. Microstructure contains detailed elements such as lexicon and metaphor, while social cognition discusses the poet's personal situation regarding his assessment of the environment and the harmony of daily life to support development of the country. Finally, social analysis refers to the practice of ideological power built by the New Order, which tends to be agrarian and worships harmony and stability in life.